1990
DOI: 10.1037/0033-2909.108.3.480
|View full text |Cite
|
Sign up to set email alerts
|

The case for motivated reasoning.

Abstract: It is proposed that motivation may affect reasoning through reliance on a biased set of cognitive processes--that is, strategies for accessing, constructing, and evaluating beliefs. The motivation to be accurate enhances use of those beliefs and strategies that are considered most appropriate, whereas the motivation to arrive at particular conclusions enhances use of those that are considered most likely to yield the desired conclusion. There is considerable evidence that people are more likely to arrive at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

241
5,297
10
99

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 6,738 publications
(5,859 citation statements)
references
References 115 publications
241
5,297
10
99
Order By: Relevance
“…This perspective is in line with classic theory and research on motivated reasoning (Kunda, 1990). Kunda eloquently argued that the mechanism underlying motivated reasoning is the differential recruitment of cognitive processes, representations and beliefs.…”
Section: List Of Figuressupporting
confidence: 81%
“…This perspective is in line with classic theory and research on motivated reasoning (Kunda, 1990). Kunda eloquently argued that the mechanism underlying motivated reasoning is the differential recruitment of cognitive processes, representations and beliefs.…”
Section: List Of Figuressupporting
confidence: 81%
“…Nisbett and Wilson (1977) demonstrated such post-hoc reasoning for causal explanations. Kuhn (1991), Kunda (1990), and Perkins, Farady, and Bushey (1991) found that everyday reasoning is heavily marred by the biased search only for reasons that support one's already-stated hypothesis.…”
Section: The Links In the Modelmentioning
confidence: 99%
“…Additionally, these effects are often found to be stronger when an individual's self-image is threatened (Beauregard and Dunning, 1998;Brown and Gallagher, 1992) and weaker when an individual's self-image is affirmed (Steele, 1988;Tesser and Cornell, 1991), suggesting that a motivation to maintain one's self-image is a driving force in these effects. These positive illusions (Greenwald, 1980;Taylor and Brown, 1988) and motivated reasoning processes (Kunda, 1990) seem to conflict with the general view that cognitive processes are designed to represent the world accurately; when it comes to ourselves, we appear instead to want to view ourselves positively, although not always (Swann et al, 1989). The extent to which these motivated reasoning processes overlap with the effect of mood and affect on judgment (Ashby et al, 1999;Forgas, 1995;Gray, 1999) is still unclear but this may be a starting point for cognitive neuroscience investigations.…”
Section: Motivated Reasoningmentioning
confidence: 99%